1988
DOI: 10.1002/1097-0142(19880215)61:4<806::aid-cncr2820610428>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in medullary thyroid carcinomas.Survival in relation to age, sex, stage, histology, immunocytochemistry, and DNA content

Abstract: Patients with medullary thyroid carcinomas (MTC) were analyzed according to age, sex, and tumor stage. In addition, the MTC were screened for the predominant histologic pattern, immunocytochemical spectrum (60 tumors), and DNA content (DNA cytophotometry and DNA flow cytometry, 25 tumors). These findings were correlated with follow-up data available for 45 of these patients. Fortyeight percent of the tumors revealed a polygonal cell pattern, whereas 22% showed spindle-cell predominance. All tumors contained cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
42
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(54 citation statements)
references
References 52 publications
8
42
1
3
Order By: Relevance
“…However, the 10-year overall survival rate varied widely among series, from 55 up to 100% respectively (Rougier et al, 1983;Saad et al, 1984;Schroder et al, 1988;Raue et al, 1993;Dottorini et al, 1996;Scopsi et al, 1996;Bergholm et al, 1997;Modigliani et al, 1998). As therapy should be adapted to the prognosis of the disease, the identification of patients at high risk of relapse is essential.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the 10-year overall survival rate varied widely among series, from 55 up to 100% respectively (Rougier et al, 1983;Saad et al, 1984;Schroder et al, 1988;Raue et al, 1993;Dottorini et al, 1996;Scopsi et al, 1996;Bergholm et al, 1997;Modigliani et al, 1998). As therapy should be adapted to the prognosis of the disease, the identification of patients at high risk of relapse is essential.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with elevated postoperative basal CT level, the 5-year relapse-free survival rate was 61%, similar to that reported by van Heerden et al (1990). The prognostic factors for survival of MTC patients include the age at diagnosis, the gender and the TNM classification (Schroder et al, 1988;Raue et al, 1993;Dottorini et al, 1996;Scopsi et al, 1996;Bergholm et al, 1997;Modigliani et al, 1998;Kebebew et al, 2000a). Data concerning MTC patients with normal postoperative imaging are few.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schröder et al (1988) found that most MTC have a diploid DNA pattern, and that a benign disease course was twice as frequent in patients with diploid tumours compared with aneuploid tumours. Conversely, the results presented by Lindsay (1970) seemed to be more consistent with aneuploidy in MTC.…”
mentioning
confidence: 99%